The Influence of Promotional Discounts, Perceived Scarcity, and Emotional Appeal on the Purchase Intention of College Students at a State University in Cebu City - Kangleon, Ma. Yassah R.; Polinar, Mark Anthony N.; Delantar, Alexander Franco A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This research aimed to explore the impact of promotional discounts, perceived scarcity, and emotional appeals on the purchasing intentions of college students attending a state university in Cebu City. The study employed a quantitative method that integrated descriptive, correlational, and predictive designs. Data were gathered from 395 students through a modified survey questionnaire, yielding a Cronbach's alpha of 0.924. The study employed descriptive statistics, Spearman’s rho correlation, and multiple regression to test the gathered data. The results showed that all three factors significantly influenced students' purchasing intentions; the highest predictor among the three was emotional appeal, followed by promotional discounts and perceived scarcity. This suggests that students may be influenced by marketing strategies that invoke urgency; however, what ultimately affects them more are those that give emotional sentiments while providing value with discounts and promotions. The study, therefore, concludes that students’ purchasing intentions are probably influenced more by marketing strategies that combine emotional engagement with a reasonable price and scarcity acting as a supporting marketing strategy. Furthermore, this research offers valuable insights into how sales promotions, feelings of scarcity, and emotional appeal impact college students' purchasing intentions.